Dithiocarbamates with potent inhibitory activity against the Saccharomyces cerevisiaeβ-carbonic anhydrase. (2nd January 2016) - Bozdag, Murat; Carta, Fabrizio; Vullo, Daniela; Isik, Semra; AlOthman, Zeid; Osman, Sameh M.; Scozzafava, Andrea; Supuran, Claudiu T.
Abstract: Dithiocarbamates (DTCs) prepared from primary or secondary amines, which incorporated amino/hydroxyl-alkyl, mono-/bicyclic aliphatic/heterocyclic rings based on the quinuclidine, piperidine, hydroxy-/carboxy-/amino-substituted piperidine, morpholine and piperazine scaffolds, were investigated for the inhibition of α- and β-carbonic anhydrases (CAs, EC 4.2.1.1) of pharmacologic relevance, such as the human (h) isoform hCA I and II, as well as the Saccharomyces cerevisiae β-CA, scCA. The yeast and its β-CA were shown earlier to be useful models of pathogenic fungal infections. The DTCs investigated here were medium potency hCA I inhibitors ( K I s of 66.5–910 nM), were more effective as hCA II inhibitors ( K I s of 8.9–107 nM) and some of them showed excellent, low nanomolar activity against the yeast enzyme, with inhibition constants ranging between 6.4 and 259 nM. The detailed structure activity relationship for inhibition of the yeast and human enzymes is discussed. Several of the investigated DTCs showed excellent selectivity ratios for inhibiting the yeast over the human cytosolic CA isoforms.